Effectiveness of Cyclosporine in a 10-year-old Girl with C3 Glomerulopathy - Kyung Mi Jang; Yong Hoon Park (Korean Society of Pediatric Nephrology, 2017)
C3 glomerulopathy (C3G) is a recently defined pathological entity characterized by C3 accumulation with absent or scant immunoglobulin deposition, leading to variable glomerular inflammation. The clinical presentation of patients with C3G is highly variable, as they may present with symptoms ranging from microscopic or mild proteinuria to full-blown nephrotic syndrome, with or without renal impairment. However, there is no consensus recommendation for specific treatment in children with C3G. Recently, new therapies have been suggested to target complement pathways, owing to an improvement in the understanding of the pathogenesis of C3G. C3G complement blockade with eculizumab, a monoclonal antibody targeted against complement C5, inhibits activation of the alternative complement pathway. We could not use eculizumab owing to its high price; thus, we administered oral prednisolone and mycophenolate mofetil (MMF). MMF was replaced with cyclosporine because proteinuria persisted, with a consistently low serum C3 level; we tapered off the prednisolone because of a Cushingoid appearance and amenorrhea. Thereafter, proteinuria improved, and the serum C3 level returned to normal. Thus, we report the effectiveness of cyclosporine in a patient with C3G and an inadequate response to prednisolone and MMF, who was detected via school urinary screening.